(untitled) (Al-Academy, 2020)
Researchers classified deconstruction as a strategy concerned with reading the philosophical, literary, artistic and critical texts according to (construction and deconstruction) binarism, which is an applied procedural space that calls for researching the layers of meaning and its non-closure. It establishes reversals in the text level. The center changes into a margin and vice versa. Thus the two researchers sought to study the deconstruction strategy and its work in the theatre field, that deconstruction is considered one of the most important modern currents that actively inters in reading the theatre show. The research studies the procedure of the construction and deconstruction of the Iraqi theatre actor regarding the Shakespearean character. The two researchers chose the Shakespearean character due to the elevated poetic language, textured dramatic construction and characters distinguished by a luxurious art. The two researchers, in order to attain the objective of the research, divided the research into a methodological framework consisting of the research problem limited to the following question: deconstructing the actor’s performance of the Shakespearean character. It also included the research objective, limits and defining the most significant terms. The theoretical framework deals with three sections. The first section: the deconstructional reading. The second section studies the Shakespearean character from the text to the show. The third section is dedicated to study the manifestations of deconstruction in the actor’s performance and the indicators of the theoretical framework. The researcher chose the play (Betrayal) as a research sample. The research included results and conclusions among which the following conclusion: Deconstruction procedures contributed in the act of (deconstruction and construction) of the Iraqi actor in opening new horizons and breaking the rules and criteria that characterize the Shakespearean character that they contributed in building performance and expressive capacities of the actor. Finally a list of sources and references